2010
DOI: 10.3136/fstr.16.135
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Kiwi Fruit on Immunity and Its Anti-oxidant Effects in Mice

Abstract: We have been investigating the immunopotentiating activity (biological response modifier (BRM)-like activity) of different fruits and attempting to clarify whether the level of this activity is consistent with the content of vitamins or other major nutrients in these fruit. In this study, we focused on kiwi fruit, which contains vitamin C and polyphenol and has a high BRM-like activity and anti-oxidant activity. We evaluated differences in this activity according to the strain and maturity. To determine the an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…Iwasawa et al . () reported that the urinary 8‐OHdG concentration in mice decreased after feeding kiwi fruit rich in polyphenols. Similar results were obtained from the studies by Fukuda et al .…”
Section: Discussionmentioning
confidence: 99%
“…Iwasawa et al . () reported that the urinary 8‐OHdG concentration in mice decreased after feeding kiwi fruit rich in polyphenols. Similar results were obtained from the studies by Fukuda et al .…”
Section: Discussionmentioning
confidence: 99%
“…A previous study by oral administration in mice suggested that kiwi fruit may have anti-oxidant effects in vivo. 16) Thus, anti-oxidant effects were examined in healthy volunteers. Anti-oxidant effects were measured using oxidative stress markers excreted in urine, 8-hydroxy-2Ј-deoxyguanosine (8-OHdG) and N-e-(hexanoyl)-lysine (HEL).…”
Section: Anti-oxidant Effects In Vivo In Healthy Volunteersmentioning
confidence: 99%
“…[14][15][16] Kiwi fruit was one of the foods found to have immunostimulatory activity. Kiwi fruit is rich in vitamins and polyphenols and has strong anti-oxidant effects.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Also, the benefits of native and exotic fruits have been reported in various studies. There is no doubt that fruits in the diet provide compounds capable of inhibiting various diseases and of contributing to a balanced diet (Iwasawa et al, 2010).…”
Section: Introductionmentioning
confidence: 99%